Lyrics Training Website; Does It Have an Effect on Students’ Listening Achievement? - Musadiq, Ahmad; Kamaluddin, Kamaluddin; Mursalim, Mursalim (Universitas Halu Oleo, 2021)
The aim of this research is to determine The Effect of Lyric Training Website on Students’ Listening Achievement at SMAN 1 Batauga. This research conducted using quasiexperimental research design. The sample are 26 students of XII MIA 1 which is assigned as experimental group and 26 students of XII MIA 2 which is assigned as control group. The research used simple random sampling design for taking the sample. The data of this research is collected by giving the students pre-test and post-test in the form of listening test. Then, the data is analyzed by using SPSS 16.0 using descriptive analyzed and inferential statistic. The results showed that the mean score of the experimental group is higher than the control group. In the experimental group the mean score of pre-test is 31.28 (Low) and the mean score of post-test is 60.25 (Moderate). In comparison, in the control group the mean score of pre-test is 33.07 (Low) and the mean score of post-test is 36.92 (low). The result of the independent sample t-test indicated that the value of sig. (2 tailed) is lower than the significance α value (0.000 < 0.05). In other words, H1 is accepted and it means that there is a significant effect of Lyric Training Website on Students’ Listening Achievement. Furthermore, the result of the finding also showed that Lyric Training can improve several things such as motivation and listening.